Implementation of Core Ethical Values by Peers in Shaping the Islamic Character of Elementary School Students - Konita Lupiah; Andi Abd. Muis; Djamaluddin; Amir Patintingan (CV. Edujavare Publishing, 2026)
The formation of students' Islamic character at the elementary school level faces various challenges, particularly in strengthening the values of honesty, responsibility, and caring in daily life, while character education in schools still tends to rely on the role of teachers, so that the potential of peers as social agents has not been optimally utilized. This study aims to describe the implementation of core ethical values by peers in shaping students' Islamic character and to analyze its implications at SD Negeri 009 Bontang Utara. This study employed a qualitative approach with a case study method. The research informants consisted of the principal, an Islamic Religious Education teacher, a fifth-grade classroom teacher, six students, and three parents. Data were collected through observation, interviews, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing and verification. The findings show that the implementation of core ethical values, namely honesty, responsibility, and caring, is carried out through six interrelated strategies: role modeling, habituation, mutual advice and reminders, cooperation, social reinforcement, and peer social control. The implementation of these values has implications for strengthening students' Islamic character, reflected in the development of honest, responsible, and caring behavior, as well as the emergence of positive social dynamics in the form of peer support circles, constructive peer pressure, and positive friendship patterns. This study confirms that positive social relationships within peer groups contribute to the sustainability of character value implementation on an ongoing basis in the elementary school environment.